Vocal responses of Hermit Thrush (Catharus guttatus) males to territorial playback of conspecific song - DeMerchant, Kendra; Roach, Sean P. (Ibis (London, England), 2022)
To better understand the use of birdsong in territorial defence, vocal responses to conspecific song playback were assessed in Hermit Thrush Catharus guttatus males. Subjects avoided both overlapping and frequency matching the playback songs. In addition, during playback, males performed abridged versions of their songs that lacked introductory notes. Overlapping and matching avoidance, as well as the use of abridged songs, may reflect subjects’ efforts to maximize signal efficiency and avoid acoustic interference, even while actively engaged in territorial defence. Future work will explore that possibility, especially with respect to the use and function of abridged songs.